PERAN WORK-LIFE BALANCE TERHADAP KETERIKATAN KERJA WANITA KARIR - Asih Puji Hastuti (Institut Islam Nahdlatul Ulama Temanggung, 2018)
In early years, based on mount career woman survey have increasing rapidly. This caused by highly education and awareness about need of self-actualization on woman. The enhancement of career woman had positive impact to well-being. In the other side, negative impact on the pursuit work life balance can be dilemma even caused dual role conflict whenever cannot balancing between work and life. The dual role conflict as a worker at once as wife and mother must be have attention. The achievement of work life balance will impact to work engagement caused highly motivation on workers and able to fight every challenge on work. This article aims to discuss the relation between work life-balance and work engagement on career woman. Often career woman had dual role conflict which triggers occur work life unbalance. The occurrence of dual role conflict on career woman can impact to performance, those very unwanted on an organization which want maximal output and if did not finished soon can be triggers occur burn out on employees.